Analisis Pengendalian Internal Proses Penerimaan Pengeluaran Persediaan dan Perbaikan Tata Letak Gudang - Puspandari, Adinda; Indriastiningsih, Erna; Primasanti, Yunita (Universitas Mercu Buana, 2023)
The process of receiving and dispensing inventory is a critical aspect of warehouse operations. Effective internal control of this process is essential to ensure inventory accuracy, reduce losses, and improve operational efficiency. This study aims to determine the internal control system in the process of receiving and dispensing PT XYZ goods, to determine the effectiveness and efficiency of the internal control system in the process of receiving and dispensing goods through improvements to PT XYZ's warehouse layout, to propose improvements to PT XYZ's logistics warehouse layout that are effective and efficient. The data collection method is carried out directly in the field by observing the implementation of internal controls in the process of receiving and issuing goods at PT. XYZ then asked questions and answers regarding the difference in the number of goods in the records and those in the warehouse and the causes of delays in the delivery of goods to employees to find out and analyze internal controls in the process of receiving and issuing goods at PT. XYZ. The research data collection technique was carried out by interviews, observation and documentation. The results showed that the results of the calculations used to design a new warehouse layout with the proposed layout combining the concepts of class A, B, and C in finished goods storage, the proposed layout can accommodate a total of 315 pallets of finished goods.